Effect of Wei Qi Booster on immune and anti-oxidative function in aged mice - Ma, Shuang; Chen, Yuming; Zhou, Zhilong; Ma, Aituan (Frontiers in Veterinary Science, 2024)
This research was conducted to examine the impact of Wei Qi Booster (WQB) on immune parameters and anti-oxidative function in aged mice. Fifty aged mice were randomly assigned to five different groups. Group A was designated as the control group. Mice in Group B were receiving Levamisole at 10 mg/kg body weight. Each mouse in groups C, D and E received 0.1%, 1%, and 2% WQB, respectively. Another ten young mice, designated as group F, were fed regularly. The mice were fed according to the above methods for 28 days. Results showed that relative to the control group, the body weight and immune organs indexes experienced a substantial rise in the group with 1% WQB. In addition, 1% WQB could improve the activity of SOD and reduce the MDA levels. Expressions of CD4 and sIgA increased while CD8 decreased in the jejunum of aged mice treated with WQB. IL2 and IFN-γ levels increased in the 1% WQB group, showing no notable difference compared to the young mice group. The results demonstrated that WQB can elevate immune levels and enhance anti-oxidative functions in aged mice.